Pedagogical concerns and market demands in VET : proceedings for the 3rd Crossing Boundaries in VET conference, Vocational Education and Training Netwerk - VETNET ; Valencia, Spain, 2-3 May 2019 - Marhuenda Fluixá, Fernando [Herausgeber]; Chisvert-Tarazona, Maria José [Herausgeber] (VETNET, 2019)
"This volume comprises 65 contributions, produced by more than 100 scholars. The papers presented and discussed at the conference offer a good amount of research results and interpretations on issues like careers and vocations nowadays and how they are addressed by VET providers and experienced by VET students, apprentices and teachers and trainers. Another issue strongly present in the conference is that of the reshaping of dual VET in those countries where it was well established in the last century and also in those trying to implement it nowadays. VET teachers and trainers is the third clear axis of contributions to this conference. Of course, there are other issues addressed like systems and agents in VET; assessment, evaluation and quality; VET and social inclusion or Continuing VET." (excerpt; BIBB-Doku)
Keywords: S System beruflicher Bildung; P 3.2.3 Lehrer; I 2.2.1 Westeuropa; I 2.3.3 Lateinamerika; I 2.2.2 Osteuropa; Berufsbildungssystem; Berufsbildung; Berufsausbildung; Berufsschullehrer; Lehrerausbildung; Höhere Berufsbildung; Service Learning; Lernen am Arbeitsplatz; Bundesrepublik Deutschland; Spanien; Brasilien; Ukraine; Finnland; Kuba; Schweiz; Schweden; Argentinien; Norwegen; USA; Vereinigtes Königreich; Ecuador; Serbien; Italien